Pengaruh Profitabilitas (ROE), Rasio Pasar (PER), dan Inflasi terhadap Harga Saham Perusahaan Manufaktur - Rasyid, Rosyeni; Patrisia, Dina; Suarni, Nora (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2013)
This study aims to analyze (1) the influence of profitability (2) market rate, (3) the rate of inflation on stock prices in the manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study considered the causative research. Types of data used is secondary data obtained from www.idx.co.id. The method of analysis used is multiple regression analysis. The results of this study concluded (1) profitability has positive and significant impact on the stock price at manufacturing companies listed on the Stock Exchange (2) the ratio of the market has positive and significant impact on the stock price at manufacturing companies listed on the Stock Exchange (3) the negative effect of inflation and no significant effect on the stock price at manufacturing companies listed on the Stock Exchange.